Photothermal-boosted effect of binary CuFe bimetallic magnetic MOF heterojunction for high-performance photo-Fenton degradation of organic pollutants - Shi, Shuo; Han, Ximei; Liu, Jie; Lan, Xi; Feng, Jianxing; Li, Yuchen; Zhang, Wentao; Wang, Jianlong (The Science of the total environment, 2021)
Overcoming the relatively low catalytic activity and strict acid pH condition of common photo-Fenton reaction is the key to alleviate the serious global burden caused by common organic pollutants. Herein, a binary homologous bimetallic heterojunction of magnetic CuFe2O4@MIL-100(Fe, Cu) metal-organic frameworks (MCuFe MOF) with photothermal-boosted photo-Fenton activity is constructed as an ideal practical photo-Fenton catalyst for the degradation of organic pollutants. Through an in-situ derivation strategy, the formed homologous bimetallic heterojunction with binary redox couples can simultaneously improve the visible light harvesting capacity and expedite the separation and transfer of photogenerated electrons/holes pairs, leading to the continuous and rapid circulation of both FeIII/FeII and CuII/CuI redox couples. Notably, the heterojunction shows intrinsic photo-thermal conversion effect, which is found to be beneficial to boost the photo-Fenton activity. Impressively, MCuFe MOF shows remarkable catalytic performance towards the degradation of various organic pollutants by comprehensively increasing H2O2 decomposition efficiency and decreasing the required dosage of MCuFe MOF (0.05 g L−1) with a wide pH range (3.0–10.0). As such, a photo-Fenton catalyst consisting of binary homologous bimetallic heterojunction is first disclosed, as well as its photothermal-enhanced effect, which is expected to drive great advance in the degradation of organic pollutants for practical applications. [Display omitted] •Bimetallic CuFe MOF was fabricated outside magnetic CuFe oxide via in-situ derivation strategy.•Photothermal effect of binary CuFe magnetic MOF catalyst can enhance the photo-Fenton activity towards POPs degradation.•FeIII/FeII and CuII/CuI binary redox couples enhance the activity of catalyst.•MCuFe MOF works effcient with reduced H2O2 dosage and broaden the pH range.